THE OPTIMIZATION PATROL OF THE SAMAPTA UNIT IN PREVENTING THE CRIME OF MOTOR VEHICLE THEFT IN THE JURISDICTION OF THE TEGAL CITY - KORNELIUS ADITYA BAGUS SETIANTO (Police Studies Review, 2022)
The background of this research is based on the high crime of motor vehicle theft (curanmor) that occurred in Tegal City. As the holder of the prevention function, the Samapta unit is one of the Police Technical Functions that is responsible for reducing the problem of theft through patrols. Patrols are carried out to prevent the emergence of someone's intention to commit the crime of theft. So, the purpose of this paper is to optimize the implementation of patrols so that the crime of theft will not occur in Tegal City. The analytical knife used by the author uses several theories and concepts including: management theory, SWOT theory, Samapta concept, curanmor concept, patrol implementation management concept and patrol concept as an analytical knife. The approach used is a qualitative approach and the method used is a field research method. The sources of data/information that the author uses are primary data, namely the results of interviews and secondary data, namely in the form of document studies in the Samapta Polres Tegal City Unit. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. From the results of the study, the implementation of patrols at the Tegal City Police has been carried out through several preparation stages, organizing stages, implementation stages and termination stages, but there are still obstacles encountered in the implementation of patrols, namely at these stages they were not carried out according to the SOP and did not get the implementation objectives. maximum patrol. Thus, the author provides problem solving as a suggestion in improving and improving the quality of the implementation of the patrols of the Samapta Police Unit of the Tegal City Police, it is necessary to hold patrol training or by asking the Head of Samapta for learning modules from Pusdik Samapta to be taught to its members so that the knowledge of its members can increase, as well as provide direction and also an understanding of what actions must be taken during the patrol.